Scientific Philosophy: Origins and Development
X, 310 p.
Keywords: Scientific Philosophy: Origins and Development is the first Yearbook of the Vienna Circle Institute, which was founded in October 1991. The book contains original contributions to an international symposium which was the first public event to be organised by the Institute: `Vienna--Berlin--Prague: The Rise of Scientific Philosophy: The Centenaries of Rudolf Carnap, Hans Reichenbach and Edgar Zilsel.' The first section of the book - `Scientific Philosophy - Origins and Developments' reveals the extent of scientific communication in the inter-War years between these great metropolitan centres, as well as presenting systematic investigations into the relevance of the heritage of the Vienna Circle to contemporary research and philosophy. This section offers a new paradigm for scientific philosophy, one which contrasts with the historiographical received view of logical empiricism. Support for this re-evaluation is offered in the second section, which contains, for the first time in English translation, Gustav Bergmann's recollections of the Vienna Circle, and an historical study of political economist Wilhelm Neurath, Otto Neurath's father. The third section gives a report on current computer-based research which documents the relevance of Otto Neurath's `Vienna method of pictorial statistics', or `Isotypes'. A review section describes new publications on Neurath and the Vienna Circle, as well anthologies relevant to Viennese philosophy and its history, setting them in their wider cultural and political perspective. Finally, a description is given of the Vienna Circle Institute and its activities since its foundation, as well as of its plans for the future.